(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2025)
About 10-35% of women report experiencing heavy periods during their reproductive years. There is still no effective treatment for this problem in modern medicine emphasizing on the importance of various traditional medications in this regard. Using modern scientific standards, the Unani compound medicine Safoof Habis ud dam’s clinical, biochemical, and haematological therapeutic efficacy and safety were evaluated in this study at the Regional Research Institute of Unani Medicine (RRIUM), Aligarh, between 2016 and 2022. A total of 77 people were selected from the patient pool who visited the outpatient department (OPD) of the institute. Starting on the days of the menstrual cycle for three consecutive cycles, patients were given 2.5 g powder of the Unani compound medicine Safoof Habis ud dam orally twice a day after meals for nine days each month. The statistical findings were evaluated using one-way analysis of variance (ANOVA) followed by Dennett’s test. The current study finds that the Unani compound medications were safe, non-toxic, and successful in treating severe menstrual bleeding. Large population studies are recommended for future research.